Organic anion exudation by ectomycorrhizal fungi and Pinus sylvestris in response to nutrient deficiencies - Schöll, Laura van; Hoffland, Ellis; Breemen, Nico van (The New phytologist, 2006)
• Low molecular weight organic anions (LMWOA) can enhance weathering of mineral grains. We tested the hypothesis that ectomycorrhizal (EcM) fungi and tree seedlings increase their exudation of LMWOA when supply of magnesium, potassium and phosphorus is low to enhance the mobilization of Mg, K and P from mineral grains. • Ectomycorrhizal fungi and Pinus sylvestris seedlings were cultured in symbiosis and in isolation on glass beads with nutrient solution or with sand as a rooting medium, with a complete nutrient supply or with Mg, K, P or N in low supply. Concentrations of all dicarboxylic LMWOA in the rooting medium were measured. • Nonmycorrhizal seedlings released predominantly malonate. Colonization with Hebeloma longicaudum decreased the amount of organic anions exuded, whereas Paxillus involutus and Piloderma croceum increased the concentration of oxalate but not the total amount of LMWOA. Phosphorus deficiency increased the concentration of LMWOA by nonmycorrhizal and EcM seedlings. Magnesium deficiency increased the concentration of oxalate by nonmycorrhizal and EcM seedlings, but not the concentration of total LMWOA. Paxillus involutus grown in pure culture responded differently to low nutrient supply compared with symbiotic growth. • Ectomycorrhizal fungi did not increase the total concentration of LMWOA compared with nonmycorrhizal seedlings but, depending on the fungal species, they affected the type of LMWOA found.